Why does knee extensor muscles torque decrease after eccentric-type exercise? - Martin, V.; Millet, G. Y.; Lattier, G.; Perrod, L. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of this study was to re-examine central and peripheral origins of neuromuscular fatigue after a highly strenuous eccentric exercise of the knee extensor muscles (KE) using both voluntary/evoked contractions and electromyographic recordings (EMG). Methods: Before, and 30 min after 15 min of intermittent one-legged downhill running, maximal percutaneous electrical stimulations (single twitch, 0.5 s tetanus at 20 Hz and 80 Hz) were applied to the femoral nerve of 10 male subjects. Electrically evoked superimposed twitches were delivered during isometric maximal voluntary contraction (MVC) to determine maximal voluntary activation (%VA). Vastus lateralis (VL), vastus medialis (VM) and biceps femoris (BF) EMG were recorded during MVC and quantified using the root mean square (RMS) value. M-wave characteristics were also determined. Results: KE MVC and %VA decreased significantly with fatigue (-19.6±6.1%; P<0.001 and -7.8±6.6%; P<0.01, respectively). Peak tetanus tension at 20 and 80 Hz (P20 and P80, respectively) declined (P<0.001), concurrently with a decrement of the P20·P80-1 ratio (-37.3±16.6%; P<0.001). Antagonist muscle coactivation, RMS to M-wave peak-to-peak amplitude and MVC·P80-1 ratios were unchanged after the fatiguing exercise. Conclusion: The results reveal that part of the large loss in MVC may have a central origin but most of the MVC decrement is due to the presence of low-frequency fatigue while possible contractile failure cannot be excluded.